Born in weak fields: below-threshold photoelectron dynamics. (13th January 2017) - Williams, J B; Saalmann, U; Trinter, F; Schöffler, M S; Weller, M; Burzynski, P; Goihl, C; Henrichs, K; Janke, C; Griffin, B; Kastirke, G; Neff, J; et al.
Abstract: We investigate the dynamics of ultra-low kinetic energy photoelectrons. Many experimental techniques employed for the detection of photoelectrons require the presence of (more or less) weak electric extraction fields in order to perform the measurement. Our studies show that ultra-low energy photoelectrons exhibit a characteristic shift in their apparent measured momentum when the target system is exposed to such static electric fields. Already fields as weak as 1 V cm –1 have an observable influence on the detected electron momentum. This apparent shift is demonstrated by an experiment on zero energy photoelectrons emitted from He and explained through theoretical model calculations.